Portrait photograph of an unidentified man (Cambridgeport, MA) - Thayer, Alexander Wheelock, 1817-1897 (previous owner):::Collector::::::::::::; Harley & Metcalf's Photograph Rooms:::Photographer:::::::::::: (Harley & Metcalf's Photograph Rooms; Cambridgeport, MA; United States, 2023)
Portrait photograph of an unidentified man (undated) by Harley & Metcalf's Photograph Rooms, corner of Main and Magazine Streets, Cambridgeport, MA, from the personal collection of Alexander Wheelock Thayer.